Efficacy and safety of abrocitinib for moderate-to-severe atopic dermatitis in adolescents and adults: Meta-analysis - Li, Ling; Yu, Jiajun; Chen, Baoqing; Guo, Ying; Yang, Yufeng (Frontiers in Pharmacology, 2023)
Objective: This study aims to investigate the safety and efficacy of abrocitinib in treating moderate-to-severe AD in adolescents and adults. Methods: Pubmed, Cochrane, Embase, and Web of science data base were searched from inception to August 9, 2022. All randomized controlled trials (RCTs) evaluating the efficacy and safety of abrocitinib in moderate to severe AD were included in the meta-analysis. Results: This meta-analysis comprised 7 studies and found that 100 mg or 200 mg of abrocitinib significantly improved IGA {[RR=2.44, 95% CI (1.93–3.08)] [RR=3.16, 95% CI (2.52-3.96)]}and EASI-75{[RR=2.18, 95%CI (1.78-2.67)] [RR=3.04, 95%CI (2.22-4.16)]} responses compared to placebo. Following that, the population was divided into adolescent and adult groups. The abrocitinib improved IGA, EASI-75 responses, and it was still superior to placebo in both the adolescent and the adult groups. PP-NRS4 response index demonstrated that abrocitinib had a greater effect than placebo at 100 mg [RR=2.22, 95% CI 1.80–2.72] and 200 mg [RR=3.28, 95% CI 2.59–4.17]. Abrocitinib improved PSAAD, POEM, DLQI, CDLQI, and HADS more than a placebo. Conclusion: In conclusion, this meta-analysis preliminarily demonstrated that abrocitinib had higher efficacy and safety in the treatment of moderate-to-severe AD in adolescents and adults. In addition, abrocitinib could rapidly relieve itching, and effectively improve symptoms and signs, with a greater effect at the dosage of 200mg than 100mg.